목 견인과 근 에너지 기법이 목 신경뿌리병증 환자의 통증, 목 기능장애지수, 관절가동범위에 미치는 영향 - 홍진기; 김영민 (대한정형도수물리치료학회지, 2021)
Background: This study examined the effects of the muscle energy technique and cervical traction after applying conservative physical therapy in patients with cervical radiculopathy. Methods: Patients were randomly divided into two groups muscle energy technique (8 subjects) and cervical traction (8 subjects). Each group performed their exercise 70 minutes per day, three times week for four weeks. Pain intensity was measured with a visual analogue scale (VAS). Function was measured with the neck disability index (NDI). Cervical range of motion (ROM) was measured with a cervical range of motion (CROM) goniometer. Results: After four weeks of therapy, VAS (p<.05) and NDI (p<.05) significantly decreased, and ROM significantly increased in both groups (p<.05). There were also significant differences between the two groups for these three measures (p<.05). Conclusion: The muscle energy technique and cervical traction are more effective than cervical traction alone in reducing VAS and NDI and increasing ROM in patients with cervical radiculopathy.